STUDY OF ENTREPRENEURSHIP ORIENTATION AND SELF-EFFICACY ON ENTREPRENEURSHIP SUCCESS AND MODERATION OF ENVIRONMENTAL INSTABILITY IN COVID 19 PANDEMIC CONDITIONS - Muhammad Fadhli (Journal of Management and Islamic Finance, 2022)
This study aims to analyze entrepreneurial orientation and self-efficacy on entrepreneurial success moderating environmental instability with entrepreneurial orientation on entrepreneurial success. This study used a descriptive quantitative method. The research was conducted in February-May 2022 in Surakarta. The population in this study were Micro Small and Medium Enterprises (MSME) actors spread in Surakarta with a total sample of 169 respondents using a simple census sampling technique based on representation of several types of MSME. The data collection technique was carried out by means of a questionnaire/questionnaire. Testing the hypothesis used the regression test and moderation regression test with SPSS software version 26.0. The results of the study conclude that entrepreneurial orientation influences entrepreneurial success. Entrepreneurial self-efficacy influences entrepreneurial success. Moderation of environmental instability on the effect of entrepreneurial orientation on entrepreneurial success is not able to moderate. The environmental instability variable is able to moderate the effect of entrepreneurial self-efficacy on entrepreneurial success.